2017
DOI: 10.3390/s17030516
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Sensing Properties of Paper Substrates and Their Passivation with ZnO Nanoparticles for Sensor Applications

Abstract: In this paper, we investigated the effect of humidity on paper substrates and propose a simple and low-cost method for their passivation using ZnO nanoparticles. To this end, we built paper-based microdevices based on an interdigitated electrode (IDE) configuration by means of a mask-less laser patterning method on simple commercial printing papers. Initial resistive measurements indicate that a paper substrate with a porous surface can be used as a cost-effective, sensitive and disposable humidity sensor in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Our imperceptible TFTs have superior linearity against humidity conditions at a gate voltage of 1V. Many researchers have studied resistive-type humidity sensors based on metal oxide with various structures, such as thin-film [34,35,36], nanoparticles [37], composites [38] and nanocrystals [39]. The sensitivity of resistive-type humidity sensors is mainly below 10 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Our imperceptible TFTs have superior linearity against humidity conditions at a gate voltage of 1V. Many researchers have studied resistive-type humidity sensors based on metal oxide with various structures, such as thin-film [34,35,36], nanoparticles [37], composites [38] and nanocrystals [39]. The sensitivity of resistive-type humidity sensors is mainly below 10 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This powerful technique used for the micromachining of microdevices consists of the creation of an effective heat zone by a focused laser beam, which induces a localized physical state transition allowing the ablation materials [ 34 ]. In order to obtain micro-scale and well-resolved electrodes, the laser ablation process was optimized as proposed in [ 35 , 36 ]. First, the pulse overlapping was adjusted by using the maximum available frequency of 65 kHz and a low raster speed of 80 mm/s in order to achieve a continuous ablation line without damaging the substrate by thermal accumulation.…”
Section: Methodsmentioning
confidence: 99%
“…The humidity sensing properties of the fabricated sensors were investigated at room temperature (25 °C) by using an indigenously custom-designed humidity setup as described in [ 36 ]. The sensor to be analyzed was placed inside a sealed Teflon chamber, along with a reference sensor (Hanna instrument) that was used to monitor in real time the temperature and relative humidity (RH) inside the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…From the dynamic response behaviour, presented in Fig. 12, it can be easily confirmed that for lower humidity levels sensor has relatively modest response, which is expected for ZnO nanoparticles [19]. For extremely high humidity conditions (RH = 90%) sensor response becomes drastic, most probably because of the several layers of physisorbed water on the surface of nanoparticles.…”
Section: Resultsmentioning
confidence: 58%